Electronic Signature Under the eIDAS Regulation in Domestic and Cross-Border Communication: Estonian Example - Kull, Irene; Kask, Laura (Journal of the University of Latvia. Law, 2019)
The aim of the article is to analyse issue of cross-border recognition and harmonized rules of electronic signatures under the eIDAS Regulation, which is intended to enable cross border electronic transactions. The authors reveal whether the legal order of the Estonia reflects the changes that have occurred in the field of electronic signatures since eIDAS Regulation. This article examines the legal consequences of a new distinction between the levels of electronic signature in the legal order of a Member State in private transactions and administrative procedures and the conditions under which cross-border recognition of electronic signatures in the European Union takes place.